The Role of Social Enterprise in Regional Development: The Case of the Czech Republic - Kraftová Ivana; Zdražil Pavel; Maštálka Martin (Institute for Policy Analysis and Social Innovation, 2015)
The article deals with development of social enterprise in the Czech Republic after 1993 and it describes the current main attitudes, including the examples of “best practices”. By means of the correlation and causal analyses it assesses its situation. It emphasises the importance of social enterprise as a factor of safe regional development.
Role sociálního podnikání v regionálním rozvoji: případ České republiky
Keywords: Social enterprise; Disadvantaged persons; Safe regional development; Unemployment; Job vacancies; sociální podnik; hendikepované osoby; bezpečnost rozvoje regionu; nezaměstnanost; volná pracovní místa